Ponomareva G.B. Dostoevsky: I Am Working on This Mystery. Review - Olga A. Bogdanova (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
This review considers the principal subjects in the latest work by Galina Ponomareva, Director of the Dostoevsky Apartment Museum in Moscow. The review’s particular focus is on the sections concerning Dostoevsky’s Moscow childhood and the “idea of Moscow” in his works.